Detecting Swelling States of Red Blood Cells by "Cell–Fluid Coupling Spectroscopy". Issue 2 (13th October 2016) - Zensen, Carla; Fernandez, Isis E.; Eickelberg, Oliver; Feldmann, Jochen; Lohmüller, Theobald
Abstract : Red blood cells are "shaken" with a holographic optical tweezer array. The flow generated around cells due to the periodic optical forcing is measured with an optically trapped "detector" particle located in the cell vicinity. A signal‐processing model that describes the cell's physical properties as an analog filter illustrates how cells can be distinguished from each other.